Performance of Banana Cultivar (Musa acuminata L. and Musa balbisiana L.) Through In Vitro Propagation - Gurning, Winda Sari Melati; Setiado, Hot; Damanik, Revandy I.M. (Jurnal Agroekoteknologi, 2019)
Performance of banana cultivars (Musa acuminata L. and Musa balbisiana L.) through in vitro propagation. Supervised by . Ir. Hot Setiado MSc and Ir. Revandy I.M Damanik Msi., Msc., PhD. The objective of the research was to determine the effect of the addition of growth regulator substances NAA and BAP on MS medium on the appearance of banana cultivar morphology and the number of shoots through multiplication in vitro. The research was conducted at  Tissue Culture Laboratory. Horticultural Seeds Centre, Medan, North Sumatera, Indonesia, from July 2017 to August 2017. The completely randomized design was used  with two factors : the first factor was cultivar (K1: banana barangan; K2: banana kepok) and the second factor was the medium (M0: control; M1: MS + NAA 0.4 ppm + BAP 2 ppm; M2: MS + NAA 0.8 ppm + BAP 5 ppm). The results showed that the cultivar and medium significantly affected the number of roots and plant height. The cultivar and medium showed the highest number of roots and the highest plant height (K1M0).